MENGAPA MASYARAKAT ENGGAN MEMBAYAR PAJAK - Tulis S. Meliala (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Tax, based on society's opinion, is not comfortable thing and like a frightfull thing. ln matter of paying tax to the government, most people don't have the willingness to do so because people don't have an Understanding about tax, there are rumours among entrepreneurs that tax can make their companies ,broke, and people don’t receive benefit of paying tax. lf the society have an understanding about tax and its history and the reason of paying tax, than tax should no longer became a frightfull thing, instead the society must feel the responsibility tor paying taxKey word: lncome Tax; Value Added Tax